Integrating Banjar Regional Songs into the Merdeka Curriculum to Strength Character Education : A Hermeneutic Study of Anang Ardiansyah's Songs - Subroto, Wisnu; Nurdin, Encep Syarief; Subiyakto, Bambang; Milyartini, Rita (Universitas Pendidikan Mandalika, 2025)
This study aims to explore the potential integration of Anang Ardiansyah's songs into the Merdeka curriculum for strengthening character education. The research method uses a qualitative approach with Paul Ricoeur's hermeneutic analysis of four selected songs. Data collection was done through a documentation study of song lyrics and related literature. The analysis used Paul Ricoeur's hermeneutic method with the stages of explanation, understanding, and appropriation. To ensure research reliability, source triangulation was conducted by comparing various references to Banjar music, local cultural values, and Merdeka Curriculum policy documents. The results identified that â€œBatasmiyahâ€ and â€œBismillah Kata Bamulaâ€ are rich in religiosity values that support the dimension of faith and piety; â€œPuhun Rambaiâ€ highlights the value of gotong royong and harmony with nature that aligns with the dimension of working together; while â€œParis Barantaiâ€ emphasizes love for the country that supports the dimension of global diversity. In addition, the songs can be integrated in various subjects through project-based and contextualized learning. The research also produced value implementation strategies through various learning activities. In conclusion, Anang Ardiansyah's songs have significant potential as a source of contextualized and meaningful character education in the formal education system. This research provides practical implications for teachers to develop meaningful learning that strengthens students' character and preserves local cultural heritage.